2015
DOI: 10.1016/j.joca.2015.02.732
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of gold nanoparticles combined with curcumin and its effect on experimental osteoarthritis in mice

Abstract: Purpose: There is a high prevalence of osteoarthritis(OA) in old population, and physicans usually treat OA based on the guideline recommended by OARSI. Until now, there is no report about the treatment in Abstracts / Osteoarthritis and Cartilage 23 (2015) A82eA416 A397

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Gold colloid or gold salts can exert anti-inflammation effect by downregulating the expression of interleukin-1β, prostaglandin E2, and cyclooxygenase-2 [ 12 15 ], which plays a crucial role in the pathogenesis of OA [ 16 21 ]. Recently, it was reported that mice model of OA, after treatment with gold nanoparticles (AuNPs) combined with curcumin, presented less severe in the histological lesions [ 22 ]. Similarly, AuNPs (7–130 nm) capped with different drugs exhibited potential treatment for OA [ 23 – 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gold colloid or gold salts can exert anti-inflammation effect by downregulating the expression of interleukin-1β, prostaglandin E2, and cyclooxygenase-2 [ 12 15 ], which plays a crucial role in the pathogenesis of OA [ 16 21 ]. Recently, it was reported that mice model of OA, after treatment with gold nanoparticles (AuNPs) combined with curcumin, presented less severe in the histological lesions [ 22 ]. Similarly, AuNPs (7–130 nm) capped with different drugs exhibited potential treatment for OA [ 23 – 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, AuNP-based medicine emerged, which is less toxic and more efficient. Indeed, AuNPs have shown excellent efficacy in arthritis treatment by inhibiting inflammatory response, both as a carrier and as a therapeutic agent, as demonstrated by various studies [ [56] , [57] , [58] , [59] ]. However, the report about the protective effect of AuNPs on cartilage, especially GP cartilage, as a response to inflammation in children is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, AuNP-based medicine emerged, which is less toxic and more e cient. Indeed, AuNPs have shown excellent e cacy in arthritis treatment by inhibiting in ammatory response, both as a carrier and as a therapeutic agent, as demonstrated by various studies [57][58][59][60]. However, the report about the protective effect of AuNPs on cartilage, especially GP cartilage, as a response to in ammation in children is limited.…”
Section: Discussionmentioning
confidence: 99%